2002
DOI: 10.1530/eje.0.1470013
|View full text |Cite
|
Sign up to set email alerts
|

Functional scintigraphy of the adrenal gland

Abstract: Over the last 30 years nuclear medicine imaging of the adrenal gland and its lesions has been achieved by the exploitation of a number of physiological characteristics of this organ. By seeking and utilising features which are quantitatively or qualitatively different from those of the adjacent tissues, functional depiction of the adrenal gland and its diseases, which in most cases retain the basic physiology of their tissue of origin, including both the cortex and the medulla, are now a useful clinical realit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 58 publications
(123 reference statements)
0
33
0
6
Order By: Relevance
“…In previous studies, two radiocholesterol derivatives have mainly been studied: 131 I-6-b-iodomethyl-norcholesterol (NP-59) and 75 Se-selenomethyl-19-norcholesterol for morphological and functional imaging of adrenal cortex (48). A disadvantage with the radiotracers is their inherent high radiation dose (49).…”
Section: Epidemiologymentioning
confidence: 99%
“…In previous studies, two radiocholesterol derivatives have mainly been studied: 131 I-6-b-iodomethyl-norcholesterol (NP-59) and 75 Se-selenomethyl-19-norcholesterol for morphological and functional imaging of adrenal cortex (48). A disadvantage with the radiotracers is their inherent high radiation dose (49).…”
Section: Epidemiologymentioning
confidence: 99%
“…Studies have demonstrated the high sensitivity (94–100%) and specificity (80–100%) of FDG-PET in differentiating benign and malignant adrenal lesions [10,11]. Adrenal radiocholesterol scintigraphy is also considered to be very accurate in distinguishing benign adrenal adenomas from extra-adrenal lesions [12]. …”
Section: Discussionmentioning
confidence: 99%
“…In den vergangenen Jahren ist es mög-lich geworden, auch kleinste endokrin aktive Tumoren der NNR aufgrund ihrer Tumorbiologie mithilfe spezifischer radioaktiv markierter Tracer in der Szintigraphie zu detektieren [14]. Die NNR exprimiert Low-density-Lipoprotein-Rezeptoren, welche durch markiertes Cholesterin sichtbar gemacht werden können.…”
Section: Lokalisationsdiagnostik Bei Verdacht Auf Androgenbildende Neunclassified
“…Die NNR exprimiert Low-density-Lipoprotein-Rezeptoren, welche durch markiertes Cholesterin sichtbar gemacht werden können. Der aktuell für die Norcholesterinszintigraphie gängige Radiotracer ist I-6-β-Iodomethylnorcholesterin (NCL-6-I) [14]. Mitunter ist eine genaue Lokalisationsdiagnostik jedoch auch unter Einsatz moderner, bildgebender tumorspezifischer Verfahren und selektiver Venenkatheterisierung nicht möglich.…”
Section: Lokalisationsdiagnostik Bei Verdacht Auf Androgenbildende Neunclassified
See 1 more Smart Citation